Molecular Epidemiology of Dengue in Panama: 25 Years of Circulation - Yamilka Díaz; María Chen-Germán; Evelia Quiroz; Jean-Paul Carrera; Julio Cisneros; Brechla Moreno; Lizbeth Cerezo; Alex O. Martinez-Torres; Lourdes Moreno; Itza Barahona de Mosca; Blas Armién; Rubing Chen; et al. (Viruses, 2019)
Dengue virus (DENV) is the most prevalent arbovirus in terms of human public health importance globally. In addition to DENV epidemiological surveillance, genomic surveillance may help investigators understand the epidemiological dynamics, geographic distribution, and temporal patterns of DENV circulation. Herein, we aimed to reconstruct the molecular epidemiology and phylogeny of DENV in Panama to connect the epidemiological history of DENV dispersal and circulation in Latin America. We retrospectively analyzed the epidemiological data obtained during 25 years of DENV surveillance in Panama. DENV was reintroduced in Panama in 1993 after a 35 year absence of autochthonous transmission. The increase in the number of total dengue cases has been accompanied by an increase in severe and fatal cases, with the highest case fatality rate recorded in 2011. All four serotypes were detected in Panama, which is characterized by serotype replacement and/or co-circulation of multiple serotypes. Phylogenetic analysis of datasets collected from envelope (E) gene sequences obtained from viruses isolated from human sera demonstrated that circulating viruses were highly diverse and clustered in distinct clades, with co-circulation of clades from the same genotype. Our analyses also suggest that Panamanian strains were related to viruses from different regions of the Americas, suggesting a continuous exchange of viruses within the Americas.